A Prospective Trial of Single-Fraction Radiation to the Tumor Bed with a Novel Breast-Specific Stereotactic Radiation Therapy Device: The GammaPod™ - Elizabeth M. Nichols, MD; Søren M. Bentzen, PhD, DMSc; Meghan Milburn, MD; Susan B. Kesmodel, MD; Emily Bellavance, MD; Stewart J. Becker, PhD; Yildirim Mutaf, PhD; Katherine Tkaczuk, MD; Paula Rosenblatt, MD; Steven J. Feigenberg, MD (Advances in Radiation Oncology, 2024)
Purpose: Radiation therapy for early-stage breast cancer is typically delivered in a hypofractionated regimen to the whole breast followed by a tumor bed boost. This results in a treatment course of approximately 4 weeks. In this study, the tumor bed boost was delivered in a single fraction as part of a safety and feasibility study for FDA clearance of the device. Methods and Materials: Eligible women with early-stage breast cancer underwent lumpectomy followed by radiation therapy. Patients underwent breast immobilization using a system specific to the GammaPod followed by CT simulation, boost treatment planning, and boost treatment delivery all in a single treatment day. Patients then started whole-breast radiation therapy within 1 week of the boost treatment. Patients and treatments were assessed for safety and feasibility. Acute toxicities were recorded. Results: A single-fraction boost of 8 Gy was delivered to the tumor bed before a course of whole-breast radiation. The GammaPod treatment was successfully delivered to 14 of 17 enrolled patients. Acute toxicities from all radiation therapy, inclusive of the boost and whole-breast radiation, were limited to grade 1 events. Conclusions: The GammaPod device successfully delivered a single-fraction boost treatment to the tumor bed with no change in expected acute toxicities. The results of this study led to FDA clearance of the device through the Investigational Device Exemption process at the FDA. The GammaPod is in clinical use at 4e institutions nationally and internationally, with additional sites pending in 2023.